A Talc- and Kaolin-Enriched Acetylated Starch Biocoating: An Alternative to Single-Use Plastic for the Food Industry - Antonio Veloso-Fernández; José Manuel Laza; Leyre Pérez-Álvarez; José Luis Vilas-Vilela (Polysaccharides)
The increasing production of plastics, driven by modern societal development, has resulted in a significant rise in plastic waste, which poses serious environmental concerns due to its lengthy degradation times. The growing issue of single-use plastics (SUPs), such as packaging for food items and disposable utensils, has led to their reduction and potential future prohibition in the European Union. Cellulose, a natural biopolymer sourced from nature, has been proposed as a viable alternative to SUPs because it degrades without toxicity. However, its limited barrier properties against water and grease have restricted its effectiveness as a substitute. This study focuses on developing an environmentally friendly alternative to SUPs by combining cellulose with acetylated starch and incorporating inorganic fillers like kaolin and talc. These fillers enhance the material’s barrier properties and reduce production costs. The results indicate that the addition of kaolin significantly lowers moisture absorption and water vapor permeability, while a mixture of kaolin and talc provides superior grease resistance. Additionally, incorporating D-sorbitol as a plasticizer improves the mechanical properties of the coated sheets, preventing cracking and enhancing strength. Overall, these coatings offer a promising alternative for packaging applications, such as for sugar, candies, or chocolate.